Menjadi Orang Tua Kreatif (Strategi Orangtua dalam Menumbuhkankembangkan Kreativitas Anak) - Novi Mulyani (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2016)
Abstract: In fact, every child is born with tremendous creative potential. Although creative levels between children with one and the other are different. However, no children were born without the creative potential. In other words, every child is creative. The family, in this case the parents have a vital and strategic role in developing the creative potential of children. This is because, however the potential of creative base that is extraordinary child, will not develop to the maximum when there is no stimulus or encouragement from the family environment. The creative potential, should be nurtured and stimulated from an early age, because at this time, the child has a tremendous opportunity to develop their potential. As the primary educator and the first for children, the elderly is the figure most responsible to the growth and development of children. Thus, parents should have creative strategies to assist, encourage, direct, and stimulate the creativity of children. Keywords: Strategy, Parents, Creativity, Kids.